Climate-Change Science or Climate-Change Propaganda? Climate Change: Evidence & Causes [Choices1]—An overview from the Royal Society and the U.S. National Academy of Sciences - Bauer, Henry (Journal of Scientific Exploration, 2015)
This booklet poses and answers 20 questions about climate change, followed by a section on “Basics of Climate Change.” If it had been published by an activist environmentalist organization, it could safely be ignored as a self-confessed piece of propaganda. But it can hardly be ignored since it comes from the top scientific institutions in the United States and Britain and might therefore be presumed to provide the most judicious available assessment of its chosen subject. Nevertheless, it is propaganda, not a scientific assessment. It argues from authority and distorts evidence in doing so. The very term “climate change” in this context is rhetorical sleight of words. Until a few years ago, “global warming” was the universally used shorthand for human-caused (anthropogenic) global warming (AGW). But since there has been no appreciable warming globally for the last 15 years or so, the critics of carbon emissions have been using the term “climate change,” which cannot be contradicted or falsified: Climate has always changed and always will. Because it is awkward to keep writing “human-caused climate change,” I will here use the previously common acronym AGW. Arguing from Authority with Just-So Stories A common tactic when arguing from authority is the Just-So Story, supporting a dogmatic assertion with apparently reasonable statements which, however, have no basis in actual facts. Rudyard Kipling’s Just So Stories are the eponymous icons for this genre, imaginatively whimsical “explanations” for how the leopard got its spots, the giraffe its long neck, the camel its hump, and so on. “But, Mr. Kipling, how do you know that’s so?” “It’s just so . . . Just So” (Hillerich 1966).